The Musical Mind: The Cognitive Psychology of Music - Sloboda, John A. (Oxford Clarendon Press, 1985)
In this comprehensive survey of the experimental literature on the cognitive psychology of music, Professor Sloboda, a psychologist and practicing musician, and "understanding" music and shows how such skills are acquired. "A break-through...brings together recent work in a way that demonstrates its significance for musicians, whilst in no way compromising the psychological theory on which it is based. The clarity of Sloboda's writing and his numerous suggestions for further research will make his book essential reading for anyone, student or researcher, interested in how minds and music interact."--Nature
Keywords: Music psychology